Design and modelling of an impedance-based MEMS biosensor - Jamil, Nadira; Nordin, Anis Nurashikin; Voiculescu, Ioana (2011)
This paper present the preliminary design of a micro-electromechanical system (MEMS) surface acoustic wave (SAW) resonator as a biosensor using COMSOL. The biosensor consists of a SAW resonator which utilizes mechanical acoustic waves as its sensing mechanism. The preliminary study was performed to verify the functionality and obtain the optimal design parameters for detection of biological cells. Placement of the cells at the centre of the device will load the acoustic waves, resulting in a damped and slower electrical signal. Our design aims to defeat limitations of the current biosensor in terms of cost, size and most important the speed of analysis. Impedance-based MEMS biosensor has the ability to monitor the cell response to electricity flow. A two dimensional finite element model (FEM) was created using COMSOL Multiphysics 3.5a to observe the change in impedance of the device model.